THE CORRELATION BETWEEN MENTAL HEALTH AND QUALITY OF LIFE IN TYPE 2 DIABETES MELLITUS PATIENTS IN THE PUSKESMAS DENGILO, POHUWATO REGENCY - Noho, Saiful Fauzie; Zainuddin, Zainuddin; Antu, Mihrawaty S (Medical and Health Journal, 2025)
Type 2 Diabetes Mellitus is still one of the chronic diseases that continues to increase every year, including in several regions of Indonesia, such as Gorontalo. The impact caused by Type 2 Diabetes Mellitus has the potential to reduce the quality of life of sufferers, especially in terms of physical, psychological, and social. Disturbed mental health, such as anxiety and depression, can worsen the condition. This study aims to determine the relationship between Mental Health and Quality of Life in Type 2 Diabetes Mellitus patients in the Dengilo Health Center work area, Pohuwato Regency. The results of this study are expected to provide insight for better interventions in the management of Type 2 Diabetes Mellitus that pay attention to mental health aspects. The research method uses a quantitative research type with a Cross Sectional research design. The population of this study was all Type 2 Diabetes Mellitus patients totaling 40 patients with a Total Sampling sampling technique. Data analysis used the Spearman's rho test. The results of the study showed a significant relationship between Mental Health and Quality of Life in Type 2 Diabetes Mellitus patients in the Dengilo Health Center work area, namely (p = 0.001). In conclusion, there is a significant relationship between Mental Health and Quality of Life in Type 2 Diabetes Mellitus patients in the Dengilo Health Center, Pohuwato Regency. It is expected that Type 2 Diabetes Mellitus patients can manage their mental condition well, and follow the right treatment so that their quality of life can increase optimally and consistently.